Penerapan IoT dan Sistem Pakar untuk Memonitoring Kualitas Air dan Mendiagnosa Penyakit pada Tambak Udang Vaname - Kevin Alexander Harianto; Rudy Adipranata; Leo Willyanto Santoso (Jurnal Infra, 2021)
Shrimp’s death is one of the things that is avoided by Vaname shrimp farmers. Where this can occur due to poort water conditions, or the way farmer maintain their shrimp.The problem that the author wants to solve is by utilizing an application that functions to see the condition of water quality using internet of things and using an expert system with the forward chaining method to diagnose if there are symptoms that arise in shrimp.Based on the test that have been carried out, the application made is able to monitor water quality properly and the results of the method test are able eto reach an accuracy value of 100%.